Denise G. answered • 10/25/21

Algebra, College Algebra, Prealgebra, Precalculus, GED, ASVAB Tutor

The find the equation of the line, you need to find the slope. This is done by taking the first derivative, using the product rule for this problem.

y' = 6x(-=sin x)+cos x (6) Now plug in x=π

y' = 6π(-=sin π)+cos π (6)

y' = 6π(0)+(-1)(6) = -6

m=-6

Now, I can plug my m, x and y values into the following equation

(y-y1)=m(x-x1)

(y-(-6π))=-6(x-π) Simplify

y+6π=-6x+6π Subtract 6π from both sides

**y = -6x **